Digital Cultural Heritage and Linked Data: Semantically-informed conceptualisations and practices with a focus on intangible cultural heritage - Ziku, Mariana (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
The emerging field of Linked Data for Digital Cultural Heritage presents new challenges and possibilities for memory institutions and the way they model their digital collections for open access. The essay reviews current semantically-informed practices and conceptualisations, standards and applied frameworks on this topic, with a focus on Intangible Cultural Heritage (ICH). In particular, the essay identifies and reviews the scope of applied frameworks for a semantically informed digital documentation of intangible cultural heritage by memory institutions, a topic with limited contributions in academic literature so far. The essay starts with an overview of the current digital transformation in the GLAM sector. Following a data centered approach, it analyses conceptual models of linked data in connection to digital heritage. It further reviews the working models and metadata schemas of linked data in particular for Intangible Cultural Heritage including innovative examples and finally, discusses challenges and new concepts for future research on the topic.